Marketing techniques, health, and nutritional claims on processed foods and beverages before and after the implementation of mandatory front-of-package warning labels in Peru - Saavedra-Garcia, Lorena; Taboada-Ramirez, Ximena; Hernández-Vásquez, Akram; Diez-Canseco, Francisco (Frontiers in Nutrition, 2022)
In June 2019, mandatory front-of-package warning labels (FOPL) were implemented in Peru. The aim of the study was to describe changes in marketing techniques (MT), health (HC), and nutritional claims (NC) on the packaging of products frequently consumed by children before and after the FOPL implementation. Product photos were taken pre- (March 2019) and post-implementation (March-October 2020) in three supermarkets in Lima. Following INFORMAS protocols and Peruvian Technical Norms, the presence of MT, HC, and NC was assessed on all package sides. Products were classified as “high-in” and “not high-in” based on the regulation threshold for critical nutrients. Differences in the proportion of products with each strategy in both periods were evaluated. We included 883 and 1035 products in pre- and post-implementation, respectively. In both periods, MT appeared on almost 70% of all products. The presence of HC increased significantly only for beverages (24.5% to 38.1%, p<0.001). In both phases, NC were commonly used on beverages (>80%). Overall, the prevalence of “high-in” products using MT increased (73.6% to 82.1%, p=0.007), while use of HC increased among “non-high-in” products (32.9% to 41.6%, p<0.001). There is a high frequency of MT on all products and NC on beverages. The increase in MT in “high-in” products may be an industry response to minimize the impact of the FOPL on food choices and sales. New regulatory aspects regarding labeling should be implemented to strengthen the current policy.